Repair of Normal and Pathologic Osseous Defects Using Bone Tissue Engineering - Kaveh, Kamran (2010)
Bone tissue engineering is the most recent technique of new bone regeneration and bone healing for bone defects. Many researches have been scoped on this matter to discover a better scaffold-cells combination in order to help patients to recover the osseous defects. Aim of current research is to evaluate the osteogenic potential of a bone tissue engineering technique consisting of corticocancellous bone autograft as scaffold that has been seeded by bone marrow as the source of mesenchymal stem cell as well as autogenous osteoblasts as the seed cells. The most successful combination was challenged in pathologic bone healing pattern. For this mean osteoporotic animal model was chosen. This research was comprised of 36 White New Zealan Rabbit in 6 groups. Group 1 was treated with corticocancellous bone graft alone. Group 2 was treated with bone marrow seeded bone graft. Third group received osteoblast seeded scaffold. Group four did not receive any treatments and served as the normal control group. Osteoporosis induced animals of Group 5 was treated with combination of osteoblast and scaffold and finally Group 6 served as osteoporotic control group without any treatment. Treatments were placed on the 15 mm critical sized defect created on mid shaft of radius. Regarding last two groups, osteoporosis was induced prior to treatment implantation. To induce osteoporosis, bilateral ovariectomy was performed that was followed by 1 mg/kg/day intramuscular injection of methyl prednisolone. Implanting the scaffold alone was performed in group one. Scaffold was harvested from iliac wing at the surgery time right before implantation. In second group, scaffold was seeded by bone marrow. Both were harvested at surgery time from iliac wing by giving the priority to bone marrow aspiration. For third group, bone marrow was aspirated approximately a month before surgery, mesenchymal stem cells isolated and proliferated and differentiated into osteoblasts in vitro. They were then seeded on the scaffold following its harvest at surgery time and then placed in the CSD. Group 4 was control and defect was left unfilled. Group 5 received same treatment of Group 3 but in osteoporotic animals. Finally in group 6, osteoporotic defect left unfilled. For 8 weeks animals were followed on both macroscopic fashions. Radiograph and gross observation was in the first category whereas light microscope and electron microscope were in the latter type. Bone healing proceeded unevenly among groups depended on the osteogenic potential of implanted treatment. Group 1 could enhance the new bone regeneration up to mid stage of endochondral ossification. Excessive callus formation, immature trabeculae and hypertrophied chondrocyte were the major finding in this group. Group 2 was proficient to enhance healing to a level further than Group 1. Combination of mature and immature trabecullae was detected at the defect at 8 weeks. Groups 3 could regenerate enough quantity of new bone to heal the critical sized defect only in 5 weeks. At week eight there was no difference between the defect and original bone. In group four, defect was filled mainly with fibroblasts and new bone regeneration was limited to host bone margins. Groups 5 developed completely mature bone trabeculae through the defect entirely; however the new formed bone was developed osteoporotic pattern and that was due to underlying disease of the host. Last group was completely unsuccessful in new bone regeneration. Immature trabeculae was only visible adjacent to the host bone and no more tissue regeneration beyond that was observed. As conclusion, osteoblast seeded scaffold served as the most potent combination in this bone tissue engineering approach. It was capable of normal bone healing only in five weeks and complete pathologic bone healing in eight week due to osteogenic, inductive and conductive potential of both scaffold and seed cells. By ruling out the over-emphasized drawbacks of autograft by finding new harvesting techniques and sites, this approach could be used to treat any kind of bone defects successfully and efficiently.